2009
DOI: 10.1097/ajp.0b013e3181a5b52a
|View full text |Cite
|
Sign up to set email alerts
|

Taking Up the Challenge of Measuring Prolonged Pain in (Premature) Neonates

Abstract: The COMFORTneo showed preliminary reliability. No major differences were found in cut-off values for low birth weight, small for gestational age, neurologic impairment risk levels, or sex. Multicenter studies should focus on establishing concurrent validity with other instruments in a patient group with a high probability of ongoing pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
142
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 42 publications
0
142
0
3
Order By: Relevance
“…Studies from NICUs in different countries likewise have shown a similar trend with a range from 6 to 17.3 procedures per patient per day [1,2,3,19,20,21]. Suctioning, venous catheter placement and heel lancing are most frequent across all settings.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Studies from NICUs in different countries likewise have shown a similar trend with a range from 6 to 17.3 procedures per patient per day [1,2,3,19,20,21]. Suctioning, venous catheter placement and heel lancing are most frequent across all settings.…”
Section: Discussionmentioning
confidence: 77%
“…Nurses assessed the neonates' pain with the Numeric Rating Scale (NRS; from 1 to 10) and the COMFORTneo Scale at least once during every 8-hour shift [18,19]. The COMFORTneo Scale has been validated, and its cutoff value for pain is a score of 14 and higher combined with an NRS score of 4 and higher.…”
Section: Methodsmentioning
confidence: 99%
“…In our hospital, a modified version of the COMFORT-behavior scale, the COMFORTneo scale, was designed and validated to assess prolonged pain in premature neonates [14]. …”
Section: Introductionmentioning
confidence: 99%
“…As differences in alarms were not expected to occur, an additional scale to measure the obtrusiveness was constructed, the soā€called collection intolerance. Because a validated scale for this purpose did not exist, a modified fiveā€point Likertā€type scale based on the facial expression section of the COMFORTneo scale was generated 13 (Table 2). A form was used to register these Likert scores (Appendix S1).…”
Section: Methodsmentioning
confidence: 99%